REVIEW: THE EFFECT OF VARIOUS COMBINATIONS OF GROWTH REGULATORY SUBSTANCES (ZPT) IN EMBRYOGENIC CALLUS INDUCTION - Andrea, Vincent (Universitas Tanjungpura, 2024)
Callus induction is the early stage of an outside systemic culture method which purpose to make and multiply callus cells en masse. Callus is a very important source of plant material in plant regeneration because every plant cell has the capability to form new singles. This review article is an effort to develop studies in plant cell and tissue culture technology, namely callus induction of plant regeneration responses in vitro. The method used is to conduct an online search using GoogleChrome on the Google Scholar site with the keywords